PENINGKATAN KINERJA GURU DALAM MENGEMBANGKAN INDIKATOR PENCAPAIAN KOMPETENSI MATA PELAJARAN AGAMA HINDU DAN BUDHI PEKERTI MELALUI PELATIHAN BERKELANJUTAN DI SD BINAAN KECAMATAN SUSUT KABUPATEN BANGLI TAHUN 2018 - Wulansari, Ida Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The purpose of this study is to improve the performance of Hindu religious teachers at Binaan elementary schools in Susut district, in Bangli regency. This study was a Regional School Action Research (PTSW) which using three cycles design and each cycle consists of four stages, namely: planning, action, gathering, and reflection. In order to obtain the data, this study used assessment techniques consist of tests of teacher ability to develop indicators of achievement of competency. It was starting by observations, development, achievement of competencies. This study was quantitative presented in the form of descriptive narratives. The results of this study shows that, the teacher’s performance can be improved in developing indicators competency of Hinduism and Buddhism. Furthermore, from 16 teachers who thoroughly examined the results of each cycle with an increase in the original value of the first cycle was 66.56% then, in cycle 2 increased to 71.25%, and in the third cycle increased to 85.63%. However, based on the result of the analysis, supervision guidance through effective training is implemented in an effort to improve the teacher performance.